2022
DOI: 10.3390/s22197501
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Adaptive Traffic Signal Control in a Connected and Automated Vehicle Environment: Optimisation of Signal Planning with Reinforcement Learning under Vehicle Speed Guidance

Abstract: Adaptive traffic signal control (ATSC) is an effective method to reduce traffic congestion in modern urban areas. Many studies adopted various approaches to adjust traffic signal plans according to real-time traffic in response to demand fluctuations to improve urban network performance (e.g., minimise delay). Recently, learning-based methods such as reinforcement learning (RL) have achieved promising results in signal plan optimisation. However, adopting these self-learning techniques in future traffic enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The simulation results indicated that travel times and delays were reduced with the application of the Adaptive Traffic Signal Control in all considered time periods, as reported in the study [31]. In his study, Dabiri et al [32], proposes a cost-effective approach to reduce delays in semi-actuated coordinated signal operation without incurring additional costs for installing new detectors or developing adaptive controller systems.…”
Section: Related Workmentioning
confidence: 58%
See 2 more Smart Citations
“…The simulation results indicated that travel times and delays were reduced with the application of the Adaptive Traffic Signal Control in all considered time periods, as reported in the study [31]. In his study, Dabiri et al [32], proposes a cost-effective approach to reduce delays in semi-actuated coordinated signal operation without incurring additional costs for installing new detectors or developing adaptive controller systems.…”
Section: Related Workmentioning
confidence: 58%
“…Common indicators include average queue length and average delays, expressed numerically or percentages. The queue length ratio is calculated by dividing the average queue length (q i ) by its maximum value (Q max ), as defined in Equation ( 21) [32].…”
Section: Queue Lengths and Delay As A Performance Indicatormentioning
confidence: 99%
See 1 more Smart Citation
“…This research also showed the evaluation and prediction of waiting time and queue length through artificial intelligence as their research gap. Recently, Maadi et al, (2022) adopted a reinforcement learning-based control system to reduce stop delay and queue length in a traffic signal. By training the traffic signal with this framework, automated and connected vehicles are provided with dynamic speed direction, which improves the interaction between the traffic controller and the driver.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Arrival rate of entity (𝜆) and service rate of server (𝜇) are the input variables to mathematically estimate waiting time, queue length, entity number in the queue and the system (Siddiqui et al, 2020). The queuing theory has many useful applications, including traffic flow (Zhao et al, 2019), (Hurtado Lange and Maguluri, 2022), (Maadi et al, 2022), plant location design (vehicle gas charging stations (Said and Mouftah, 2020), (Xiao et al, 2020)), scheduling (jobs on machine, patients in hospitals, online order taking and computer programs), and facility design (post offices, banks, supermarkets, ticket counter). Using queuing theory, a company can develop more efficient processes, systems, pricing mechanisms, staffing solutions, and arrival management strategies to minimize customer's waiting time and maximize the number of customers served.…”
Section: Introductionmentioning
confidence: 99%